2017
DOI: 10.1590/0103-6440201601136
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Biofilm on Implant Abutment Surfaces Coating with Diamond-Like Carbon and Biocompatibility

Abstract: The aim of this study was to evaluate the surface free energy (SFE), wetting and surface properties as well as antimicrobial, adhesion and biocompatibility properties of diamondlike carbon (DLC)-coated surfaces. In addition, the leakage of Escherichia coli through the abutment-dental implant interface was also calculated. SFE was calculated from contact angle values; R a was measured before and after DLC coating. Antimicrobial and adhesion properties against E. coli and cytotoxicity of DLC with human keratinoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…It should ideally include the deposition of an intermediate layer, such as amorphous silicon, to promote adhesion of DLC to the substrate [143]. The aim has been to produce surfaces of improved corrosion resistance and enhanced biocompatibility, and there is experimental evidence that success with these aspects can be achieved in vitro [142,144,145]. However, despite this promise, this approach has not yet had any impact on clinical practice, and DLC-coated dental implants are not yet being used in patients.…”
Section: Surface Modification Of Titanium Alloysmentioning
confidence: 99%
“…It should ideally include the deposition of an intermediate layer, such as amorphous silicon, to promote adhesion of DLC to the substrate [143]. The aim has been to produce surfaces of improved corrosion resistance and enhanced biocompatibility, and there is experimental evidence that success with these aspects can be achieved in vitro [142,144,145]. However, despite this promise, this approach has not yet had any impact on clinical practice, and DLC-coated dental implants are not yet being used in patients.…”
Section: Surface Modification Of Titanium Alloysmentioning
confidence: 99%
“…DLC surfaces have a diversity of properties, such as great hardness, near to the ground friction coefficients, chemical inertness, great resistance to wear, and good biocompatibilities, which make them promising candidates for biomedical applications (Allen et al, 1994; Butter and Lettington, 1995; Wei et al, 2016; Derakhshandeh et al, 2017; Huacho et al, 2017). DLC films are promising applicants for modifying the surface of artificial joints, which the cell responses to its surface properties have attracted attentions of scientists in recent years (Liao et al, 2016).…”
Section: Carbon-family Nanomaterials At the Nano-bio Interfacementioning
confidence: 99%
“…Butter and Lettington (Butter and Lettington, 1995) have investigated the efficacy of using DLC-coated pins into soft tissue and femurs of sheep, which their results indicated much superior bonding at DLC than metal–tissue borders with inferior risk of infection. Huacho et al (2017) have more recently studied the surface free energy (SFE), wetting and surface properties, antimicrobial, adhesion and biocompatibility characteristics of DLC surfaces for biomedical applications. Their results indicated that the DLC surfaces cause a small reduction in cell viability, whereas the SFE, roughness (R a), bacterial adhesion, antimicrobial, and bacterial infiltration investigations presented no noteworthy dissimilarities.…”
Section: Carbon-family Nanomaterials At the Nano-bio Interfacementioning
confidence: 99%
“…[27] Casarin et al [28] reported that ultrasonic scalers can cause roughness of tooth surfaces, a process that can be affected by working factors such as procedure time, pressure, and angulation of the scaling tip. Oral bacterial adhesion and retention is affected by the surface roughness of any hard surfaces in the oral cavity and has a significant outcome on the formation and progression of dental plaque as well as influencing discoloration of esthetic restorations.. [29][30][31] Consequently, this in vitro study has been performed to detect the effect of routine scaling using hand or ultrasonic tips on the enamel surface roughness (Ra).…”
Section: Discussionmentioning
confidence: 99%